The Intention of Young Muslim Generation to Choose Muslim-Friendly Destinations in Indonesia - Dewi, Nur Diana (Faculty of Economic and Business Syarif Hidayatullah State Islamic University of Jakarta, 2025)
Research Originality: Although much research has examined Muslim-friendly tourism, this research conducts a more comprehensive study of the intentions of the young Muslim generation to choose Muslim-friendly tourist destinations.Research Objectives: The research objective is to analyze what factors influence the young Muslim generation's intention to choose Muslim-friendly tourist destinations in Indonesia.Research Methods: The data analysis technique used a Structural Equation Model (SEM) with SmartPLS 3.0 software. Data was obtained by distributing questionnaires to 200 respondents.Empirial Result: The results showed that the variables of subjective norms, behavioral control, and religiosity had a significant effect on the intentions of the young generation in choosing Muslim-friendly tourist destinations in Indonesia, while the attitude variable had no significant effect.Implications: The results of this research imply that the government must create regulations that attract the young generation of Muslims to visit Muslim-friendly tourist destinations in Indonesia.JEL Classification: M30, M31How to Cite:Dewi, N. D. (2025). The Intention of Young Muslim Generation to Choose Muslim-Friendly Destinations in Indonesia. Signifikan: Jurnal Ilmu Ekonomi, 14(1), 265-278. https://doi.org/10.15408/sjie.v14i1.45353.